2013
DOI: 10.3396/ijic.v9i2.012.13
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii bloodstream infections in a tertiary hospital: Antimicrobial resistance surveillance

Abstract: Nosocomial bacteremia caused by Acinetobacter baumannii is of increasing concern in critically ill patients. there is a world-wide increase in the emergence of multidrug-resistant (MDR) A. baumannii to antimicrobials. therefore we conducted this study to evaluate the resistance pattern of A. baumannii in patients with bacteremia. this is a retrospective study conducted in a tertiary hospital in Saudi Arabia. During the period from April 2006 till April 2010, data for A. baumannii isolated from blood were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
11
3
Order By: Relevance
“…The results of our study reveal three main findings. First, the percentage of MDR-AB in our study was 98.3% of all VAP cases, which is higher than previously reported in VAP (20%-80.5%) [12,22,23] and other nosocomial infections (15.7%-75%) [10,[24][25][26] in different countries. Second, independent predictors of 14-day mortality in MDR-AB VAP patients were an inadequate number of definitive therapies and not using nebulized Consistent with previous studies [11], an inadequate number of definitive treatments was identified as one of the independent factors associated with higher mortality in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…The results of our study reveal three main findings. First, the percentage of MDR-AB in our study was 98.3% of all VAP cases, which is higher than previously reported in VAP (20%-80.5%) [12,22,23] and other nosocomial infections (15.7%-75%) [10,[24][25][26] in different countries. Second, independent predictors of 14-day mortality in MDR-AB VAP patients were an inadequate number of definitive therapies and not using nebulized Consistent with previous studies [11], an inadequate number of definitive treatments was identified as one of the independent factors associated with higher mortality in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, the resistance to imipenem was 76.19% throughout the hospital and 87.7% in the ICUs. This rate is lower than that noted in India, where the resistance to imipenem reached 89.6% [ 20 ] and higher than those of previous studies in Morocco: 23.6% [ 22 ] in 2001, 42.6% in 2005 [ 7 ] and those obtained in the United States and Saudi Arabia, where the resistance to imipenem was 44.7% and 61.3% respectively [ 18 , 21 ]. Carbapenem resistance in A. baumannii is often due to the expression of OXA carbapenemase types, Metallo-beta-lactamases (MBL) carbapenemase and the impermeability associated with mutations altering the expression of porins and efflux pumps [ 3 , 30 ].…”
Section: Discussioncontrasting
confidence: 59%
“…The resistance to colistin was confirmed by the determination of the Minimum Inhibitory Concentrations (MICs) using the E-test method (Biomérieux, Marcy l'Etoile, France) according to the manufacturer′s recommendations. All isolates of Acinetobacter resistant to three or more classes of antibiotics represented by piperacillin / tazobactam, ceftazidime, imipenem, ciprofloxacin, aminoglycosides and colistin were considered as MDR [ 18 , 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imipenem (61.3%) and meropenem (3.9%) also revealed high resistance rates. Out of the total, 104 (78.8%) of these multi-drug resistant (MDR) strains were sensitive only to colistin and tigecycline (Al-Mously, 2013).…”
Section: Most Common Pathogens Isolatedmentioning
confidence: 99%